Session Topic: Asset Management and Monetary Policy: Discussion - Huntsman, Blaine; Moore, Basil J.; Soldofsky, Robert M. (Journal of Finance, 1969)
Blaine Huntsman, Basil J. Moore, Robert M. Soldofsky, Session Topic: Asset Management and Monetary Policy: Discussion, The Journal of Finance, Vol. 24, No. 2, Papers and Proceedings of the Twenty-Seventh Annual Meeting of the American Finance Association Chicago, Illinois December 28-30, 1968 (May, 1969), pp. 239-247